2021
DOI: 10.1089/crispr.2020.0144
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed Base Editors for Precise Editing of the Sickle Cell Disease Mutation

Abstract: Base editors are fusions of a deaminase and CRISPR-Cas ribonucleoprotein that allow programmable installment of transition mutations without double-strand DNA break intermediates. The breadth of potential base editing targets is frequently limited by the requirement of a suitably positioned Cas9 protospacer adjacent motif. To address this, we used structures of Cas9 and TadA to design a set of inlaid base editors (IBEs), in which deaminase domains are internal to Cas9. Several of these IBEs exhibit shifted edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 29 publications
(55 reference statements)
3
40
0
Order By: Relevance
“…Importantly, engraftment capacity of base edited HSPCs in immunodeficient mice was not altered in comparison with uneditied cells either with from HD CB and mPB CD34+ cells were used. These results are consistent with recent studies performed in healthy and sickle cell HSPCs 41, 48, 49 . Further studies will directly address the important question of engraftment potential for base edited FA cells.…”
Section: Discussionsupporting
confidence: 94%
“…Importantly, engraftment capacity of base edited HSPCs in immunodeficient mice was not altered in comparison with uneditied cells either with from HD CB and mPB CD34+ cells were used. These results are consistent with recent studies performed in healthy and sickle cell HSPCs 41, 48, 49 . Further studies will directly address the important question of engraftment potential for base edited FA cells.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, we observed obviously reduced off-target editing of both molecules in two of our inlaid Sa-CBEs. Consistent with this observation, three recent reports also demonstrated that inlaid SaCas9 and SpCas9 base editors showed decreased Cas9-independent RNA or DNA off-target editing 37 - 39 . In our R-loop assay, we noted that the editing efficiency for each cytosine in the artificial R-loop varied significantly, possibly because of the different accessibilities between the editable cytosines and the deaminase.…”
Section: Discussionsupporting
confidence: 72%
“…First, structural analyses of Nme2Cas9 [84] indicate that the position of the N-terminally fused TadA8e domain relative to the predicted path of the displaced strand is not optimal. With other effectors, domain-inlaid deaminase fusions have proven to be advantageous in some contexts [29,54], and the same is likely to be true with Nme2-ABEs. Second, the current Nme2-ABE8e has a wide editing window that could result in increased bystander editing.…”
Section: Discussionmentioning
confidence: 99%